Mullite (3Al2O3·2SiO2) ceramics obtained by reaction sintering of rice husk ash and alumina, phase evolution, sintering and microstructure - Serra, María Florencia (2016)
The use of industrial waste (by-products) as raw materials in the ceramic industry has been under study for decades due to the economical, energy, tax and environmental advantages. The specificity of the waste requires a basic characterization and technology thereof.The applicability of rice husk ash (RHA), as silica (SiO 2) source, in refractory and porous materials with potential structural, insulating and/or filtering applications was carried out by characterizing the ceramic behavior of stoichiometric mixtures of calcined alumina (Al2O3) and RHA. A reaction-sintering framework can be defined in the (3Al2O3·2SiO2) system. The sinterability and conversion during the reaction sintering processes were studied in order to obtain mullite (3Al2O3·2SiO2) ceramics. Also some microstructural features of the developed materials were studied in the 1100-1600 °C range. The mullitization was studied quantitatively.Partial densification was achieved (30%) and highly converted materials were obtained. The developed microstructure consisted in a dense ceramic matrix with homogenous interconnected porosity, with a narrow pore size distribution below 20 μm. The developed material gives enough information for designing mullite ceramics materials with either porous or dense microstructures with structural, insulating or filtering applications employing RHA as silica source and calcined alumina as the only other raw material.